ChemInform Abstract: Diversity‐Oriented Synthesis of Macrocycle Libraries for Drug Discovery and Chemical Biology. Issue 29 (29th June 2016) - Collins, Suil; Bartlett, Sean; Nie, Feilin; Sore, Hannah F.; Spring, David R.
Abstract: Review: [109 refs.